Determinants of health care utilization by immigrants in Portugal - Dias, Sónia F (2017)
Background: The increasing diversity of population in European Countries poses new challenges to national health systems. There is a lack of data on accessibility and use of health care services by migrants, appropriateness of the care provided, client satisfaction and problems experienced when confronting the health care system. This limits knowledge about the multiple determinants of the utilization of health services. The aim of this study was to describe the access of migrants to health care and its determinants in Portugal. Methods: The study sample included 1513 immigrants (53% men), interviewed at the National Immigrant Support Centre, in Lisbon. Data were collected using questionnaires. The magnitude of associations between use of National Health Service and socio-demographic variables was estimated by means of odds ratios (OR) at 95% confidence intervals, calculated using logistic regression. Results: Among participants, 3.6% stated not knowing where to go if facing a health problem. Approximately 20% of the respondents reported that they had never used the National Health Service, men more than women. Among National Health Service users, 35.6% attended Health Centres, 12% used Hospital services, and 54.4% used both. Among the participants that ever used the health services, 22.4% reported to be unsatisfied or very unsatisfied. After adjusting for all variables, utilization of health services, among immigrant men, remained significantly associated with length of stay, legal status, and country of origin. Among immigrant women, the use of health services was significantly associated with length of stay and country of origin. Conclusion: There is a clear need to better understand how to ensure access to health care services and to deliver appropriate care to immigrants, and that special consideration must be given to recent and undocumented migrants. To increase health services use, and the uptake of prevention programs, barriers must be identified and approaches to remove them developed, through coherent and comprehensive strategies.